(untitled) (Analele Universității din București. Științe Politice, 2024)
Amidst the pandemic resulting in a global health crisis, Bangladesh was unnerved by the fake COVID-19 test result certificates issued by the private Regent Hospital in Dhaka. The healthcare corruption was exposed when Il Messaggero (The Messenger) daily newspaper in Rome reported that infected Bangladeshi migrants were moving about in the city undetected and posed a health risk. What is the impact of healthcare corruption during a pandemic for the vulnerable people of a developing country in a globalized economy? This article will assess the plight of the Bangladeshi migrant labour force and ready-make garment sector domestic work force within the framework of vulnerability interdependence. The authoritarian interlude will be contextualized for disrupting democratic consolidation in the country, which sustained the environment that led to the issuance of fake healthcare certificates. In ascertaining the endemic corruption in Bangladesh, this study will posit leadership integrity in taking a public goods approach to trammelling corruption.